Characterization of mixed xWO3(1-x)Y2O3 nanoparticle thick film for gas sensing application - Shahrokh Abadi, Mohammad Hadi; Hamidon, Mohd. Nizar; Shaari, Abdul Halim; Abdullah, Norhafizah; Misron, Norhisam; Wagiran, Rahman (Multidisciplinary Digital Publishing Institute, 2010)
Microstructural, topology, inner morphology, and gas-sensitivity of mixed xWO(3)(1-x)Y(2)O(3) nanoparticles (x = 1, 0.95, 0.9, 0.85, 0.8) thick-film semiconductor gas sensors were studied. The surface topography and inner morphological properties of the mixed powder and sensing film were characterized with X-ray diffraction (XRD), atomic force microscopy (AFM), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). Also, gas sensitivity properties of the printed films were evaluated in the presence of methane (CH(4)) and butane (C(4)H(10)) at up to 500 °C operating temperature of the sensor. The results show that the doping agent can modify some structural properties and gas sensitivity of the mixed powder.